COVID-19 serology in nephrology healthcare workers - Reiter, Thomas (Wien Klin Wochenschr, 2021)
BACKGROUND: Chronic kidney disease patients show a high mortality in cases of a severe acute respiratory syndrome coronavirus-2 (SARS-CoV‑2) infection. Thus, information on the sero-status of nephrology personnel might be crucial for patient protection; however, limited information exists about the presence of SARS-CoV‑2 antibodies in asymptomatic individuals. METHODS: We examined the seroprevalence of SARS-CoV‑2 IgG and IgM antibodies among healthcare workers of a tertiary care kidney center during the the first peak phase of the corona virus disease 2019 (COVID-19) crisis in Austria using an orthogonal test strategy and a total of 12 commercial nucleocapsid protein or spike glycoprotein-based assays as well as Western blotting and a neutralization assay. RESULTS: At baseline 60 of 235 study participants (25.5%, 95% confidence interval, CI 20.4–31.5%) were judged to be borderline positive or positive for IgM or IgG using a high sensitivity/low specificity threshold in one test system. Follow-up analysis after about 2 weeks revealed IgG positivity in 12 (5.1%, 95% CI: 2.9–8.8%) and IgM positivity in 6 (2.6%, 95% CI: 1.1–5.6) in at least one assay. Of the healthcare workers 2.1% (95% CI: 0.8–5.0%) showed IgG nucleocapsid antibodies in at least 2 assays. By contrast, positive controls with proven COVID-19 showed antibody positivity among almost all test systems. Moreover, serum samples obtained from healthcare workers did not show SARS-CoV‑2 neutralizing capacity, in contrast to positive controls. CONCLUSION: Using a broad spectrum of antibody tests the present study revealed inconsistent results for SARS-CoV‑2 seroprevalence among asymptomatic individuals, while this was not the case among COVID-19 patients. TRIAL REGISTRATION NUMBER: CONEC, ClinicalTrials.gov number NCT04347694 SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s00508-021-01848-5) contains supplementary material, which is available to authorized users.